Assessment of railway plain concrete arch bridges subjected to high-speed trains. (October 2020) - Yazdani, Mahdi; Azimi, Peyman
Highlights: FE modeling has performed to evaluated dynamic response of masonry arch bridges. By categorizing the geometry of high-speed trains, 27 models have been detected. The performance of the bridges at speeds of 150 up to 400 km/h have been assessed. 324 transient dynamic analysis for high-speed trains has been conducted. The responses of the bridges are totally depended on the spacing of axles in bogies. Abstract: There are plentiful masonry arch bridges around the world that have been used as railway bridges for more than 80 years. In Iran's railway network, 3, 700 bridges exist which all of these have been designed based on service load in the past (low-speed trains) and are still serving for trains at a maximum speed of 100 km/h. In the present study, two plain concrete arch bridges are investigated using finite element technique. For validation of numerical models, the crown deflection of the two bridges under static loading and the locomotive moving as well as the first three modes of the bridges were selected as a calibration criterion and compared with experimental results. In the second step, by categorizing the trains based on geometrical properties, 27 models of Asian and European high-speed trains and Euro-code suggestions have been detected to make sure all of the possible geometries have been counted. Afterward, 324 time-history dynamic analyses have been performed in order to assess the dynamic behavior of the bridges under the high-speed trains at speeds of 150, 200, 250, 300, 350 and 400 km/h. Finally, deflection and acceleration responses of the bridges for all 324 dynamic analyses at the main crown of the bridges have been extracted. The results indicate that the dynamic performance of these bridges under high-speed trains is affected by span length, vehicle motion speed, material stiffness, train coach distribution, and axles' distances. The responses are increased by increasing the vehicle speed and the spacing of axles in bogies. In the case of acceleration and displacement responses, the effect of span length parameter appeared to be significant at every speed. The results achieved from the time-history analyses showed more sensitivity in the dynamic performance of the bridge with longer span length (2L20) to acceleration response and in the bridge with lower span length (5L06) to displacement response.